2011
DOI: 10.1002/gps.2705
|View full text |Cite
|
Sign up to set email alerts
|

The influence of psychological, social and contextual factors on the expression and measurement of awareness in early‐stage dementia: testing a biopsychosocial model

Abstract: The findings support the relevance of a biopsychosocial approach to understanding the factors that influence unawareness of impairment in dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
140
4
21

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(181 citation statements)
references
References 39 publications
16
140
4
21
Order By: Relevance
“…In recent years, a series of studies have explored the awareness of people living with dementia about many different aspects of their illness (Clare, 2002;2003;: 2012Sabat, 2002a;2002b;2006;Cheston, 2005;Clare et al, 2005;Macquarrie, 2005;Vernooij-Dassen et al, 2006;Clare et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a series of studies have explored the awareness of people living with dementia about many different aspects of their illness (Clare, 2002;2003;: 2012Sabat, 2002a;2002b;2006;Cheston, 2005;Clare et al, 2005;Macquarrie, 2005;Vernooij-Dassen et al, 2006;Clare et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were reported in studies on dyadic rating discrepancies in rating activities of daily living (ADL). Some researchers reported caregiver burden to be associated with the discrepancy scores (Schatzberg et al, 1998;Zanetti et al, 1999;Clare et al, 2011), although only Zanetti et al (1999) assessed both caregiver burden and depression. In contrast, Argüelles et al (2001) showed that caregiver depression but not burden was related to caregiver rating bias.…”
Section: Introductionmentioning
confidence: 99%
“…External psychological influence leading to recovery can be observed in patients with major changes to the brain such as strokes, injuries or conditions such as dementia that clearly affect and impair their functioning (Chriki et al, 2006;Letswaart et al, 2011;Bender and Constance, 2005;Clare et al, 2012;Schiff, 2010;Samuel, 2008;Morse and Garner, 2018). Minor neural changes such as those caused in drugs and alcohol addicted patients have been reversed by external psychological influence through rehabilitation courses in meditation and mindfulness (Winkelman, 2001;Garland et al, 2014;Garland and Howard, 2018).…”
Section: Man Is a Masterpiece Of Creation If For No Other Reason Thanmentioning
confidence: 99%